Determination of ELISA reactive mumps IgG antibodies in MMR vaccine recipients in comparison with MMR vaccine naïve children: a cross sectional study - Bhargava, Riya; Saxena, Naveen; Gupta, Parul; Bhargava, Abhishek (International Journal of Research in Medical Sciences, 2021)
Background: Mumps is a vaccine preventable infectious disease characterized by parotitis. In India mumps vaccines are not currently used under NIP. Waning of vaccine-induced immunity is considered to play a central role in the reemergence of mumps. The comprehensive data on the seroepidemiology of measles, mumps, and rubella (MMR) as well as studies which compare the antibody titer among mumps vaccine naïve with mumps vaccinated children are lacking. The aim of our study is to estimate and compare Mumps specific antibody titer in children with and without MMR vaccine. Current study is a cross sectional observational study. Methods: In 2019/2020, blood samples were collected from 100 healthy children attending immunization clinic in government medical college Kota and associated J. K. Lon maternal and child care hospital Kota. The samples were investigated for MMR IgG antibodies using ELISA. Results: Out of total 100 children included in the study 32.27% vaccinated and 4.83% Non-vaccinated were positive for Mumps IgG antibody in the age group of 6m to 6 year. While in the age group of 6year to 12 year there was 31.57% and 26.57% positivity respectively. The seroprevalence of measles, mumps and rubella antibodies among 50 MMR vaccinated children was 94%, 64%, and 96% respectively. A high measles and rubella seroprevalence was observed among all children age groups, suggesting an effective control program, while the mumps seroprevalence decreased significantly with age. Conclusions: The maximum vaccine effectiveness against mumps for 2 doses of MMR vaccine is≈96% therefore the herd immunity threshold to block mumps virus transmission is ≥86%. As per our study only 64% of the vaccinated children were found to have IgG Mumps Ab. In view of morbidity following mumps infection there is a need to incorporate mumps vaccine along with measles and rubella vaccine in the NIP instead of MR.